Comparison between Doppler and Non-Stress Test in Pregnant Women with Oligohydramnios for Assessment of Perinatal Outcome at Post Date Pregnancy - Ahmed, Dhuha Nadhim; Wadi, Suha Abdul Jaleel (Journal of Science in Medicine and Life, 2025)
Background: High-risk pregnancies, especially with oligohydramnios, significantly increase infant mortality and morbidity. Obstetrics focuses on preventing complications, with Doppler and NST being key in assessing fetal health. Oligohydramnios, varying in incidence and severity, can lead to diverse perinatal outcomes, including increased cesarean sections rate and fetal pulmonary complications. Aim of the study: To compare the value of fetal doppler ultrasound and fetal non-stress test in prediction of perinatal outcome in oligohydramnios at postdate pregnancy. Patients and methods: This cohort study was conducted at Al-Elwiya Maternity Teaching Hospital from 1st January to 1st December 2023, including 100 post-date pregnant women with oligohydramnios. Exclusions includes active labor, contraindications to vaginal delivery, and refusal to participate. Data collection covered demographics, medical history, surgical history, physical exams, Doppler ultrasound findings, and non-stress tests. Outcomes for both mother and neonate, including delivery type, complications, and neonatal health, were recorded, ensuring ethical considerations and confidentiality. Results: This study classified post-date pregnant women with oligohydramnios into four groups based on NST and Doppler results. Group 1 (reactive NST, normal Doppler) comprised 32%, Group 2 (normal NST, abnormal Doppler) 26%, Group 3 (abnormal NST, normal Doppler) 30%, and Group 4 (both abnormal) 12%. It found significant differences in delivery modes, with more cesarean sections in Groups 2 and 4. NICU admissions and IUGR incidence varied notably across groups, highlighting the importance of these tests in predicting adverse perinatal outcomes. Conclusion: NST and Doppler effectively assess perinatal outcomes in oligohydramnios, guiding delivery methods and NICU admissions, and highlighting variable risks.